Dinamika Peran Orang Tua Menanamkan Kemandirian Anak Autis - Aah Barokah; Budi Sarasati (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
This research aims to analyze the dynamics of parental roles in fostering independence in children with autism. The focus of this study is on the experiences and practices of parents regarding their efforts to support the independence of their autistic children. This study employs a qualitative method with a phenomenological approach. Data collection methods include in-depth interviews, observations, and documentation. The research involves two subjects and three informants. The two subjects are parents with autistic children aged 13 and 14 years old. The results of this study indicate that the independence of autistic children can be built through self-acceptance, which forms discipline, consistency, and guidance provided by parents from an early age. Another supporting factor is the deconstruction of the father’s role in the process of raising autistic children. The father’s role is crucial in shaping the discipline and independence of autistic children.